Evaluating the Impact of Integrating Intelligent Educational Chatbots in English Conversation-Based Classes on Reducing Speaking Anxiety Among Adult Language Learners - Molaei, Akbar (International Journal of Education and Cognitive Sciences, 2026)
Purpose: This study aimed to evaluate the effectiveness of integrating intelligent educational chatbots into English conversation-based classrooms in reducing speaking anxiety among adult language learners. Methods and Materials: A randomized controlled trial was conducted with 30 adult intermediate-level English learners from Tehran, who were randomly assigned to either an experimental group (n = 15) receiving a 10-session chatbot-assisted intervention or a control group (n = 15) participating in traditional conversation classes. Each session lasted 90 minutes and focused on interactive speaking tasks. Speaking anxiety was measured using the Foreign Language Classroom Anxiety Scale (FLCAS) at three time points: pre-test, post-test, and five-month follow-up. Data were analyzed using repeated measures ANOVA and Bonferroni post-hoc tests via SPSS-27. Findings: The results showed a significant time × group interaction effect on speaking anxiety scores (F(2, 56) = 35.41, p < .001, η² = .57), indicating that the reduction in anxiety was significantly greater in the experimental group than in the control group. Participants in the chatbot-assisted group experienced a significant decline in anxiety from pre-test (M = 126.47) to post-test (M = 97.85), which was sustained at follow-up (M = 99.42). Bonferroni post-hoc comparisons confirmed significant within-group changes for the experimental group (p < .001), while the control group showed no statistically significant differences across time points. Conclusion: The integration of AI-powered educational chatbots in conversation-focused English classes appears to be an effective and lasting strategy for reducing speaking anxiety among adult learners. These findings suggest that chatbots offer a psychologically safe, interactive, and engaging environment that facilitates oral language development by lowering affective barriers in language learning.